Saxifraga shennongii, a new species of Saxifragaceae from Hunan Province, China - Zhang, Jijun; Zhao, Wanyi; Meng, Kaikai; Liao, Wenbo; Wang, Lei; Chen, Sufang (Phytotaxa, 2019)
Saxifraga shennongii L. Wang, W.B. Liao et J. J. Zhang, a new species of Saxifragaceae from Hunan, China, is described and illustrated. The new species belongs to genus Saxifraga sect. Irregulares and can be distinguished from other species by stolons absent, basal leaf blade subrounded and abaxially spotted, absence of foliar embryos in the sinus, petiole sparsely short glandular pilose or glabrous and inflorescence branches up to 10 cm long. Phylogenetic analysis based on four chloroplast DNA regions (rbcL, psbA-trnH, matK and psaJ-rpl33) confirmed that the new species differed from those similar species of Saxifraga sect. Irregulares. The new species is similar to S. daqiaoensis and S. mengtzeana, but differs in indumentum and the shape of leaf.